انتّطبيقبت انهّغىية في ان عًبجى الإنكترونيّة وإحراء انكفبية ان عًج يًّة - شبرنيّة سيّذ يح ذًّ انسيّذ (International Journal on Humanities & Social Sciences, 2024)
This research takes on a strong basis in the importance of the electronic lexicon to the knowledge society and aims to demonstrate the importance of linguistic applications in electronic lexicons and to recognize its role in the development and development of lexicon adequacy so as to receive more attention from e-lexicon manufacturers and users. The descriptive approach is adopted in the presentation of these applications in a number of lexicons, reaching the following: These applications contribute to motivation and motivation to acquire lexical knowledge. The diversity of presentation methods and their attractiveness bring lexical proliferation and diversity, help reduce linguistic errors, and stimulate the organization and storage of lexical knowledge in the mind lexicon through remembrance, repetition, prediction, and feedback. The research recommends further exploitation of computer technologies in applications that facilitate access to lexical knowledge such as operative translation and spelling. It suggests studies on some applications such as the application: The most searched words to see user trends of elexicons in word search.